2016
DOI: 10.1186/s13059-016-0892-5
|View full text |Cite
|
Sign up to set email alerts
|

The aspirin-induced long non-coding RNA OLA1P2 blocks phosphorylated STAT3 homodimer formation

Abstract: BackgroundAlthough the chemopreventive effects of aspirin have been extensively investigated, the roles of many cell components, such as long non-coding RNAs, in these effects are still not completely understood.ResultsWe identify an aspirin-induced upregulated lncRNA, OLA1P2, in human colorectal cancer. Aspirin induces demethylation of the FOXD3 promoter and promotes expression of the FOXD3 gene. Subsequently, upregulated FOXD3 protein transcriptionally activates lncRNA OLA1P2 expression. OLA1P2 upregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 33 publications
5
79
1
1
Order By: Relevance
“…The lnc‐DC binds directly to STAT3 and promotes STAT3 phosphorylation at Y705 by preventing STAT3 from binding to phosphatase small heterodimer partner 1 . OLA1P2 binds to STAT3, inhibits the phosphorylation of Y705, and blocks phosphorylated STAT3 homodimer formation . Here, we showed that TSLNC8 binds to the DNA‐binding domain of STAT3 but not the C‐terminal domain containing the Y705 and S727 sites, which binds with lnc‐DC or OLA1P2, and that the STAT3 recognized site at the 748‐758 nucleotides of TSLNC8 is important for the biological function of this lncRNA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The lnc‐DC binds directly to STAT3 and promotes STAT3 phosphorylation at Y705 by preventing STAT3 from binding to phosphatase small heterodimer partner 1 . OLA1P2 binds to STAT3, inhibits the phosphorylation of Y705, and blocks phosphorylated STAT3 homodimer formation . Here, we showed that TSLNC8 binds to the DNA‐binding domain of STAT3 but not the C‐terminal domain containing the Y705 and S727 sites, which binds with lnc‐DC or OLA1P2, and that the STAT3 recognized site at the 748‐758 nucleotides of TSLNC8 is important for the biological function of this lncRNA.…”
Section: Discussionmentioning
confidence: 78%
“…As a promising molecular target for the treatment of various cancers, STAT3 is activated in many cancer types . Several lncRNAs regulate the phosphorylation status of STAT3 and alter its nuclear import–export dynamics . The lnc‐DC binds directly to STAT3 and promotes STAT3 phosphorylation at Y705 by preventing STAT3 from binding to phosphatase small heterodimer partner 1 .…”
Section: Discussionmentioning
confidence: 99%
“…1 More than 50% of patients with lung cancer are diagnosed with a very poor prognosis, and approximately 30% of the patients do not get adequate treatment. [2][3][4] Lung cancer has become a life-threatening disease and seriously influences people's quality of life. Researchers have spared no efforts to determine the mechanism of lung cancer and to accelerate the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The list of aspirin targets keeps increasing. Aspirin reportedly acetylates P53 and histone, and induces FoxD3 promoter demethylation and FoxD3 expression thereby inducing lncRNA OLA1P2, which inhibits the nuclear import of phosphorylated STAT3 . Moreover, aspirin inhibits NF‐κB signaling thereby relieving acquired drug resistance in breast cancer .…”
Section: Complex Mechanisms For the Anticancer Effects Of Aspirinmentioning
confidence: 99%